Forgotten Fundamental Meaning of Graphic Design in Indonesia - Yasser Rizky (Bina Nusantara University, 2012)
This article forwards questions about graphic design in Indonesia. Most people here, even graphic designers or graphic design academics do not know the answer to the question of what graphic design is. This condition brings out a new question of whether we really have a graphic design culture in Indonesia. If we trace back to the cause of it all, we will find a fact how a human interest discourse is still very rare in our country. Even when we find one, it tends to be a very subjective compilation of opinions instead of a strongly-based study. In further look, this is one of the reasons of why many graphic designers are stirred into ineffective work process causing unequal partnerships in their professional projects. For this, we have none to blame but ourselves and the system that we’ve created.